Hi Khaz'goroth.

8 Worgen Warrior
0
Hi.
Reply Quote
85 Night Elf Druid
10845
Have you seen my baseball?
Reply Quote
85 Worgen Druid
2645
/bark
Reply Quote
85 Night Elf Druid
3135
Ishnu-alah
Reply Quote
96 Gnome Warrior
13530
05/02/2011 07:26 AMPosted by Ivoryline
Have you seen my baseball?


Sorry, I borrowed it to make a gun.
Reply Quote
85 Troll Shaman
3100

05/02/2011 11:06 PMPosted by Fitzy
Have you seen my baseball?


Sorry, I borrowed it to make a gun.


Can you modify it to shoot water balloons? that would be kickass!
Reply Quote
85 Human Death Knight
0
Hello.
Reply Quote
96 Gnome Warrior
13530
05/03/2011 05:22 AMPosted by Frostblood


Sorry, I borrowed it to make a gun.


Can you modify it to shoot water balloons? that would be kickass!


I can modify anything for anything!
Reply Quote
90 Troll Warlock
10620
Posted by FrostbloodSorry, I borrowed it to make a gun.Can you modify it to shoot water balloons? that would be kickass!I can modify anything for anything!


does that make u mc giver (or however its spelt)
Reply Quote
85 Undead Rogue
10415
05/14/2011 10:36 AMPosted by Eleclya
Posted by FrostbloodSorry, I borrowed it to make a gun.Can you modify it to shoot water balloons? that would be kickass!I can modify anything for anything!


does that make u mc giver (or however its spelt)


Macgyver.
Reply Quote
90 Troll Warlock
10620
lol i knew i spelt it wrong ..my bad ..but hey i didnt realise it was a real tv show till recently.. thought the simpsons made him up ;)
Reply Quote
70 Gnome Mage
8510
!@#$% please
Reply Quote
1 Draenei Shaman
0
great another terrible khaz twink necroing 8 month old threads
Reply Quote
85 Human Priest
6875
In need of urgent help!

When the quadratic equation y = (x - 3)(4x + 2) is written in standard form, what is the value of the coeffici?
Reply Quote
90 Blood Elf Priest
10420
In need of urgent help!

When the quadratic equation y = (x - 3)(4x + 2) is written in standard form, what is the value of the coeffici?


y=(x-3)(4x+2)
y =4x(squared)+2x+12x-6
y =4x(squared)+14x-6
Sub into quadratic equation
1. x = 0.39 2. x= -3.89

1. y = 4(0.39)(squared)+14(0.39)-6
y=2.43+5.46-6
y=1.89

2. y = 4(-3.89)(squared)+14(-3.89)-6
y= 242.11-54.46-6
y =181.65

That what you meant or not? :P I didn't really understand the question.




Reply Quote
85 Human Priest
6875
y=(x-3)(4x+2)
y =4x(squared)+2x+12x-6
y =4x(squared)+14x-6
Sub into quadratic equation
1. x = 0.39 2. x= -3.89

1. y = 4(0.39)(squared)+14(0.39)-6
y=2.43+5.46-6
y=1.89

2. y = 4(-3.89)(squared)+14(-3.89)-6
y= 242.11-54.46-6
y =181.65

That what you meant or not? :P I didn't really understand the question.


That's great; thank you very much!
Reply Quote
85 Human Paladin
3035
unna
Reply Quote

Please report any Code of Conduct violations, including:

Threats of violence. We take these seriously and will alert the proper authorities.

Posts containing personal information about other players. This includes physical addresses, e-mail addresses, phone numbers, and inappropriate photos and/or videos.

Harassing or discriminatory language. This will not be tolerated.

Forums Code of Conduct

Report Post # written by

Reason
Explain (256 characters max)

Reported!

[Close]